FUZZY MATHEMATICAL MODELS FOR SLIP VELOCITY IN BOUNDARY LAYER FLOWS: A FOURIER TRANSFORM APPROACH - T N, Vasanthakumari (ShodhKosh: Journal of Visual and Performing Arts, 2022)
We formulate fuzzy mathematics to deal with boundary layer flows with slip velocity and thermal effects and use Fourier transforms to reduce the governing equations. In addition, fuzzy logic is an essential part of this approach because it solves the problem of uncertainties that are present in important parameters (i.e., slip velocity and thermal diffusivity) and it helps to formulate a realistic and adaptable model. This method has by far shown better results that classical models and identifies velocity and thermal profiles under different regimes. The framework is robust as it was validated against experimental data and is applicable in aerodynamics, thermal engineering, and material sciences. The relevant fuzzy models for real-world fluid dynamics problems, as demonstrated in the study, emphasize both their flexibility and computational efficiency. The limitations and future recommendations for the work, such as using more advanced fuzzy models and hybrid techniques, are also discussed, which would help extend the applicability of this methodology to non-linear fluid systems found often in engineering processes.